West Nile Virus activity in Latin America and the Caribbean - Komar, Nicholas (2006)
Notes that West Nile Virus has spread rapidly throughout the Caribbean Basin since its initial detection there in 2001. Summarizes current knowledge of its transmission in tropical America.